Recommendation on instrument-based screening for depression during pregnancy and the postpartum period - Lang, Eddy; Colquhoun, Heather; LeBlanc, John C.; Riva, John J.; Moore, Ainsley; Traversy, Gregory; Wilson, Brenda; Grad, Roland (Canadian Medical Association journal (CMAJ), 2022)
Depression during pregnancy and the postpartum period can have far-reaching impacts on the child-bearing individual and their infant, as well as on parent-infant interactions and relationships with partners. Consequences for the child-bearing individual include increased likelihood of future anxiety or depression, lower quality of life, increases in risky behaviors and suicidal ideation. Impacts on the infant could include delays in physical and mental development, such as cognitive and language development, and overall infant health concerns. Impacts on parent-infant interactions can include reduced breastfeeding and poor parent-infant bonding. Here, Lang et al provide guidance to primary care health professionals, policy-makers and patients on screening for depression in individuals during pregnancy and up to 1 year postpartum.